MILITANTS, CRIMINALS, AND WARLORDS : THE CHALLENGE OF LOCAL GOVERNANCE IN AN AGE OF DISORDER - Felbab-Brown, Vanda; Trinkunas, Harold A.; Hamid, Shadi, 1983- (Geopolitics in the 21st century, 2018)
Conventional political theory holds that the sovereign state is the legitimate source of order and provider of public services in any society, whether democratic or not. But Hezbollah and ISIS in the Middle East, pirate clans in Africa, criminal gangs in South America, and militias in Southeast Asia are examples of nonstate actors that control local territory and render public services that the nation-state cannot or will not provide.